2009
DOI: 10.1007/s11300-009-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Unemployment Duration in Slovenia using Cox Regression Models

Abstract: Survival analysis, Cox regression model, Unemployment duration, C14, C24, J60, J64,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…(Roed et al, 1999), na Noruega, destacam que as chances de encontrar um emprego são reduzidas no desemprego de longa duração, e identificam que as mulheres demoram mais tempo para encontrar emprego que os homens. (Boršič e Kavkler, 2009) aumento do nível educacional e a idade. Os autores argumentam que taxas de saída mais altas entre pessoas mais instruídas podem ser explicadas por sua capacidade mais efetiva de procurar emprego devido ao melhor acesso às informações e, também, por possuírem um maior custo de oportunidade em permanecerem sem trabalho.…”
Section: Duração Do Desemprego No Mercado De Trabalho: Breve Revisão ...unclassified
“…(Roed et al, 1999), na Noruega, destacam que as chances de encontrar um emprego são reduzidas no desemprego de longa duração, e identificam que as mulheres demoram mais tempo para encontrar emprego que os homens. (Boršič e Kavkler, 2009) aumento do nível educacional e a idade. Os autores argumentam que taxas de saída mais altas entre pessoas mais instruídas podem ser explicadas por sua capacidade mais efetiva de procurar emprego devido ao melhor acesso às informações e, também, por possuírem um maior custo de oportunidade em permanecerem sem trabalho.…”
Section: Duração Do Desemprego No Mercado De Trabalho: Breve Revisão ...unclassified
“…In their study, Borsic and Kavkler (2008) estimated the effect of the demographic characteristics of individuals on their unemployment durations for Slovenia between the years 2002-2005 using the Cox regression model. In the study, it was concluded that there are significant differences in the duration of unemployment between age groups.…”
Section: Introductionmentioning
confidence: 99%